Transformational leadership and teacher well-being: A systematic review - Olga Meidelina; Airin Yustikarini Saleh; Cintya Amelia Cathlin; Sekar Aulia Winesa (Journal of Education and Learning (EduLearn), 2023)
Teachers play a significant role and face diverse challenges everyday, therefore escalating the research of teacher well-being and its factors, with leadership being one of them. This review aims to summarize the findings focusing on the differences and teacher’s perspectives on teacher well-being and transformational leadership in schools. The review consists of peer reviewed articles from 2012 to 2021, with kindergarten to high school teachers as participants. Several databases were used, which are Scopus, Science Direct, PsycInfo, World of Science (WoS) Journal, PubMed, SAGE journals, Education Resources Information Centre (ERIC), and Garuda. Articles were selected using preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines and 10 were included in the qualitative synthesis. Studies showed that transformational leadership positively correlated with teacher well-being. Research regarding the efficiency of transformational leadership’s each aspect in increasing teacher well-being can be interesting to study in the future.